Community Based Flood Catastrophe Preparedness, Vulnerability, Management and Response of Layyah District, Punjab, Pakistan (1990-2015): Community Based Flood Catastrophe Preparedness, Vulnerability, Management and Response of Layyah District, Punjab, Pakistan (1990-2015) - Gull, Misbah; Khan , Saifullah; Nawaz, Muhammad; Hasan, Mahmood Ul (International Journal of Economic and Environmental Geology, 2024)
The study articulates the society supported flood disaster preparedness, vulnerability, management, and response in the Layyah district, southern Punjab, Pakistan. The area has recorded high summer temperature, low rainfall and an arid climate with an optimistic departure of one centimeter. At Taunsa barrage, the Indus river, as well as the Thal canal, show a decline in the annual flow, while it remains high at Chashma barrage having a heavy flow from July to October. Historically, the foremost disasters experienced in Layyah district are floods, earthquakes, droughts, epidemics, and fires. About 81 Potwar areas have been affected every year by flood disaster consisting of 36 medium and 45 high risks units. Obviously, the locals are the primary instrument to fight any catastrophe for their safety at the initial stage as they are admirable arbitrators of risk assessment, vulnerability, rehabilitation, excavation, and can acquire consistent estimations for their safety. The joint endeavors of the locals and government during pre disaster and a post-disaster stage will make certain that how to provide crucial support as well as services to the distressed community throughout the Layyah district. The social or anthropogenic level arrangements for flood catastrophes are appreciated mutually at national and international levels.